The Dynamic Response of Municipal Budgets to Revenue Shocks - Ines Helm; Jan Stuhler (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the fiscal and tax response to intergovernmental grants, exploiting quasi-experimental variation within Germany's fiscal equalization scheme triggered by Census revisions of official population counts. Municipal budgets do not adjust instantly. Instead, spending and investments adapt within five years to revenue gains, while adjustment to revenue losses is more rapid. Yet, the long-run response is symmetric. The tax response is particularly slow, stretching over more than a decade. Well-known empirical “anomalies” in public finance such as the flypaper effect are thus primarily a short-run phenomenon, while long-run fiscal behavior appears more consistent with standard theories of fiscal federalism.
Keywords: H71; H72; H77; E62; 330; intergovernmental grants; fiscal transfers; government spending; local taxation; census shock; flypaper effect